Pengaruh Tingkat Pendidikan, Pengetahuan Akuntansi, Pengalaman Informasi Terhadap Penggunaan informasi Akuntansi Pada Masjid Se Kota Mataram - Animah Animah; Widia Astuti; D Tialurra Della Nabilla (Universitas Muhammadiyah Jember, 2023)
This research aims to examine the influence of education level, accounting knowledge and accounting information experience on the use of accounting information in Mosques in Mataram City. The Grand Theory used in this research is decision usefulness theory. The type of research used in this research is quantitative descriptive research. The data source obtained for this research is a primary data source by filling out a questionnaire distributed and filled in by the Mosque Management (Treasurer) in Mataram City. The research population was all mosques in Mataram City. Purposive sampling technique with criteria: mosques that manage funds from the community in the form of infaq, shadakah, zakat fitrah and zakat mal. The total of sampel was 50 mosques. The analytical tool used is multiple linear regression. The research results show that the variable experience in accounting influences the use of accounting information. Meanwhile, education level, accounting knowledge has no effect on the use of accounting information. Simultaneously the results show a fairly low influence, this is because the use of accounting information in a mosque is not mandatory. The implications of using accounting information should be a necessity in mosques.